Pembelajaran Berbasis STEM untuk Meningkatkan Literasi Numerasi Siswa Sekolah Dasar: A Systematic Literature Review - Amanda Mei Puspita; Filda Indriya Laili; Sumaji Sumaji (Algoritma : Jurnal Matematika, Ilmu pengetahuan Alam, Kebumian dan Angkasa, 2026)
Numeracy literacy is a fundamental ability required by elementary school students to solve everyday problems, yet field outcomes often indicate a need for improvement. One innovative instructional method that offers a potential solution is Science, Technology, Engineering, and Mathematics (STEM) based learning. This study aims to comprehensively analyze the literature regarding the effectiveness of implementing the STEM approach in enhancing numeracy literacy among elementary school students. This study employed a Systematic Literature Review (SLR) method guided by the PRISMA protocol. The article search was conducted across three main academic databases: Google Scholar, Garuda, and DOAJ. The inclusion criteria comprised peer-reviewed journal articles published in the last decade (2016-2026), focusing on students in grades 1 to 6, and specifically measuring numeracy literacy aspects. The synthesis of the 18 selected studies demonstrates that STEM-based learning is highly effective in significantly improving students' numeracy literacy. This method facilitates students in understanding mathematical concepts more thoroughly through interdisciplinary integration, real-world application, and project-based activities. The findings indicate the necessity for educators and policymakers to design specific instructional materials and conduct teacher training to seamlessly integrate the STEM framework into classroom teaching, thereby creating an optimal learning environment for 21st-century skills.